Factorial invariance of the Physical Self-Concept Scale in Mexican students (Invarianza factorial de la escala de autoconcepto físico en hombres y mujeres estudiantes universitarios) - Elia Verónica Benavides Pando; José René Blanco Ornelas; Jesús Enrique Peinado Pérez; Julio César Guedea Delgado; Martha Ornelas Contreras (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The present study analyses the psychometric properties proposed by Blanco, Blanco, Viciana, and Zueck (2015) for the Physical Self-Concept Scale (CAF). The total sample consisted of 1,500 Mexican university students, with a mean age of 20.69 years (± SD = 2.33). Confirmatory factorial analyses showed that a two-factor structure is viable and adequate for both studied groups (men and women). The structure of two factors (motor competence and physical attractiveness), according to statistical and substantive criteria, has shown adequate indicators of reliability and validity adjustment. In addition, the factorial structure, factor loads and intercepts are considered invariant in the two groups studied. However, differences between the two groups for the factor means were found. Further research should replicate these findings in larger samples.